IDENTIFIKASI BERPIKIR KRITIS DALAM MENYELESAIKAN SOAL MATEMATIKA SUB POKOK BAHASAN ARITMETIKA SOSIAL BERBASIS LINGKUNGAN SISWA KELAS VII MTs NEGERI JEMBER 1 - Anggraeni, Citra Dwi; Susanto, Susanto; Kurniati, Dian (Kadikma, 2017)
Abstract. This study aims to identify the critical thinking of the seventh grade students of MTs Negeri Jember 1 in solving the mathematics problem sub subject of social arithmetic. The standard of critical thinking used in this study is bassam's that is clarity, precision, accuracy, relevance, consistency, logical correctness, completeness, and fairness. The instruments used in this study are math tests and interview guides. Subjects in this study are students of class VII MTs Negeri Jember 1 semester even in the academic year 2016-2017. In the social arithmetic material of the students of class VII MTs Negeri Jember 1 tends not to meet all the critical thinking standards that Bassam has, but for the matter of applying the selling price of the students of class VII tends to write down what is known and asked, ordinary interest of grade VII students tends not to meet all Bassam's critical thinking standards. Key Words: Identification, Critical Thinking, Student MTs, and Social Arimetics